The Management Structure of the Network Societies of Small Enterprises and the Role of Trust: the Comparison of Russian and German Cases. - Фридерике Вельтер; Теему Каутонен; Александр Юльевич Чепуренко; Елена Мальева (Journal of Economic Sociology, 2010)
The paper discloses the impact of trust on management structures of the inter-firm relations in the sector of small business in the country with the developed market relations (Germany) and transition economy (Russia). The authors put into focus the impact of the trust types on the management of the inter-firm network relations of the German and Russian small enterprises. The empirical basis of the study is the standard poll of 197 German and 400 Russian small enterprises as well as the materials of the in-depth interviews, conducted within the international project in 2001-2003.